2015
DOI: 10.1007/s10854-015-3400-x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and properties of Sn58Bi, Sn35Bi0.3Ag, Sn35Bi1.0Ag solder and solder joints

Abstract: Microstructures, interface reaction, melting characteristics, tensile property, thermal fatigue behavior and wettability of Sn58Bi, Sn35Bi0.3Ag and Sn35Bi1.0Ag solders were investigated. Only Sn phase and Bi phase like net-type distribute uniformly in the Sn58Bi matrix, Sn35Bi0.3Ag and Sn35Bi1.0Ag solder show the Ag 3 Sn particles in the Sn matrix around net-like Bi phase, at the solder/Cu solder joints, only Cu 6 Sn 5 intermetallic compound was observed. The liquid phase line temperature of Sn35Bi0.3Ag and Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Shalaby [48] found that the addition of In elements had critical effect on the onset point of the Sn-58Bi solder which meant that adding 2 wt.% In could decrease the onset point of the solder from 139.06 ∘ C to 129.68 ∘ C. But the onset point of the Sn-58Bi solder with addition of 2 wt.% Ag elements did not change remaining at 139.06 ∘ C. So it was considered that the 2 wt.% Ag addition had little effect on the onset point of the Sn-58Bi solder. At the same time, adding 2 wt.% In and 2 wt.% Ag to the Sn-58Bi solder reduced the melting temperature of the composite solder from 143.75 ∘ C to 133.59 ∘ C. Zhang et al [34] pointed out that the effects of the 0.3 wt.% and 1.0 wt.% Ag addition on the solid phase line temperature of the Sn35Bi solder were slight because the solid phase line temperatures of the Sn35Bi, Sn35Bi0.3Ag, and Sn35Bi1.0Ag composite solders were 138.5 ∘ C, 138.8 ∘ C, and 138.9 ∘ C, respectively. But the liquidus temperature of the above solders was 150.3 ∘ C, 183.6 ∘ C, and 184 ∘ C; it could be seen that the effects of the 0.3 wt.% and 1.0 wt.% Ag addition on the liquidus temperature were obvious.…”
Section: Soldermentioning
confidence: 99%
See 2 more Smart Citations
“…Shalaby [48] found that the addition of In elements had critical effect on the onset point of the Sn-58Bi solder which meant that adding 2 wt.% In could decrease the onset point of the solder from 139.06 ∘ C to 129.68 ∘ C. But the onset point of the Sn-58Bi solder with addition of 2 wt.% Ag elements did not change remaining at 139.06 ∘ C. So it was considered that the 2 wt.% Ag addition had little effect on the onset point of the Sn-58Bi solder. At the same time, adding 2 wt.% In and 2 wt.% Ag to the Sn-58Bi solder reduced the melting temperature of the composite solder from 143.75 ∘ C to 133.59 ∘ C. Zhang et al [34] pointed out that the effects of the 0.3 wt.% and 1.0 wt.% Ag addition on the solid phase line temperature of the Sn35Bi solder were slight because the solid phase line temperatures of the Sn35Bi, Sn35Bi0.3Ag, and Sn35Bi1.0Ag composite solders were 138.5 ∘ C, 138.8 ∘ C, and 138.9 ∘ C, respectively. But the liquidus temperature of the above solders was 150.3 ∘ C, 183.6 ∘ C, and 184 ∘ C; it could be seen that the effects of the 0.3 wt.% and 1.0 wt.% Ag addition on the liquidus temperature were obvious.…”
Section: Soldermentioning
confidence: 99%
“…Chen et al [33] studied the wettability of Sn-Bi-3Zn ( = 37, 38,39,41,42,43) and Sn-38Bi-Zn ( = 0, 23, 4) at 170 ∘ C and 190 ∘ C. At 170 ∘ C, the spreading ratio was increased from 68% to 72% with the Bi element increased; but the spreading ratio was decreased from 75.8% to 66% and then increased to 72.7% with the Zn element increased. At 190 ∘ C, the spreading ratio of the Sn-Bi-3Zn alloys was decreased from 73.2% to 72% and then increased to 73.3% and it was higher than that at 170 ∘ C. However, the spreading ratio of the Sn-38Bi-Zn alloys changed slightly remaining 72% at 190 ∘ C. The wettability of the Sn-58Bi, Sn-35Bi-0.5Ag, and Sn-35Bi-1.0Ag was investigated by Zhang et al [34]. The above three solders with different fluxes showed different wettability with air and N 2 atmosphere.…”
Section: Wettabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Other important Pb-free alloys include components like Cu, Bi, Zn, In, and Sb. Some of these have shown promising results, like lower melting points Metals 2020, 10, 370 2 of 11 than Sn-Pb; however, the inherent brittleness of Bi, the scarcity of In in the earth's crust, the mild toxicity of Sb, and the oxidation issues associated with Zn have prevented their application [7,8,[11][12][13][14][15][16]. Among these binary alloys, the Sn-Cu alloy seems to be a great candidate because of its cheaper price, absence of harmful Ag 3 Sn IMCs, and good wetting.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising Sn-Bi solder with low Bi content is Sn-35Bi-1Ag alloy because it possesses a comparable melting point as Sn-Pb eutectic solder. The microstructure and tensile properties of solder, wetting kinetics of solder on Cu, interfacial reaction in solder joints and thermal cycling reliability were then studied [15][16][17][18]. However, Sn-35Bi-1Ag solder still exhibited lower tensile and ductility [19].On the other hand, to improve the properties of Sn-Bi solder, many researchers tried to incorporate the alloying elements into Sn-58Bi eutectic solder.…”
mentioning
confidence: 99%